Destination image and revisit intention: the case of Egypt tourism - Ahmed, Mohammed (PASOS Revista de Turismo y Patrimonio Cultural, 2023)
This study aims to investigate the relationship between destination image, perceived value, satisfaction, and revisit intention in the tourism field, as well as examine the factors that affect tourists’ intention to revisit Egypt. The study also analyzes the mediating effects of tourist satisfaction and perceived value. Based on an extensive literature review, a study model and questionnaire were designed. Data were collected from international tourists and were analysed using structural equation model (SEM). The key findings show that both cognitive-affective destination image and perceived value affect tourists’ intention to revisit. The findings also indicate that the cognitive destination image and perceived value are substantial factors in influencing tourist satisfaction. Additionally, a mediating role of affective image and perceived value was found in this study. Academic contributions, management implications, and some potential ideas for future studies are also discussed.